Therapeutic vaccination with 4–1BB co-stimulation eradicates mouse acute myeloid leukemia. (3rd October 2018) - Kerage, Daniel; Soon, Megan S. F.; Doff, Brianna L.; Kobayashi, Takumi; Nissen, Michael D.; Lam, Pui Yeng; Leggatt, Graham R.; Mattarollo, Stephen R.
ABSTRACT: Immunomodulatory therapies can effectively control haematological malignancies. Previously we reported the effectiveness of combination immunotherapies that centre on 4-1BB-targeted co-stimulation of CD8 + T cells, particularly when simultaneously harnessing the immune adjuvant properties of Natural Killer T (NKT) cells. The objective of this study was to assess the effectiveness of agonistic anti-4-1BB antibody-based combination therapy against two aggressive forms of acute myeloid leukemia (AML). Anti-4-1BB treatment alone resulted in transient suppression of established AML-ETO9a tumor growth in 50% of mice, however the majority of these mice subsequently succumbed to disease. Combining alpha-galactosylceramide (α-GalCer)-loaded tumor cell vaccination with anti-4-1BB antibody treatment increased the proportion of responding mice to 100%, and protection led to long-term, tumor-free survival, demonstrating complete eradication of AML. This finding was extended to established mixed lymphocytic leukemia (MLL)-AF9 tumors, whereby vaccine plus anti-4-1BB combination similarly resulted in 100% protection. The addition of anti-PD-1 to anti-4-1BB treatment, although improving survival outcomes compared to anti-4-1BB alone, was not as effective as NKT cell vaccination. The effectiveness of 4-1BB combination therapies was dependent on IFN-γ signaling within host cells, but not tumors. Vaccine plus anti-4-1BB therapy elicited potent generation of functional effector and memory CD8 + T cells in all tumor-associated organs. Therapy induced KLRG1+ effector CD8 T cells were the most effective at controlling disease. We show that combining NKT cell-targeting vaccination with anti-4-1BB provides excellent therapeutic responses against AML and MLL in mice, and these results will guide ongoing efforts in finding immunotherapeutic solutions against acute myeloid leukemias.